Spectral Characterization of Fungal Metabolites in Aqueous Medium with Humus Substances - D. A. Khundzhua; S. V. Patsaeva; V. A. Terekhova; V. I. Yuzhakov (Journal of Spectroscopy)
The work is targeted to confirm participation of microscopic fungi in transformation of humus substances in aquatic environments. The research is focused on the spectroscopic study of the collection of fungal strains with different pigmentation of mycelium. Spectral properties of fungal metabolites were measured and compared to that of natural aquatic nonliving organic matter and commercial humus substances in aqueous solutions. The experiments revealed that the effect of microscopic fungi growing in the culture medium with added humate appeared as changes in the humic-type fluorescence: its characteristics became more similar to that of nonliving organic matter in natural waters than to original humate preparation. The experiments demonstrated degradation of coal-originated humate due to microbial activity into compounds of smaller molecular size and increased heterogeneity. We resume that transformation of humus substances by fungal cultures can be monitored and characterized using spectral measurements.